Ion source developments at IPP: On the road towards achieving the ITER-NBI targets and preparing concepts for DEMO. Issue 1 (1st April 2022) - Fantz, U; Briefi, S; Fröschle, M; den Harder, N; Heiler, A; Heinemann, B; Hurlbatt, A; Hopf, C; Lindqvist, M; Merk, F; Mimo, A; Nocentini, R; et al.
Abstract: The large ion source of ITER's neutral beam injection (NBI) systems (0.9 m×1.9 m) with 1280 apertures has to deliver 57 A D - for 3600 s (286 A/m 2 ) and 66 A H - for 1000 s (329 A/m 2 ). The RF ion source test facilities ELISE and BUG at IPP are aimed to demonstrate the ion source parameters, the homogeneity of large beams (up to 1 m×1 m) and to perform beam optic studies. While the ITER parameters could be demonstrated in hydrogen, the achievement in deuterium for long pulses is still pending due to the large fraction of co-extracted electrons, their temporal dynamics, and inhomogeneity in vertical direction, limiting the ion source performance. Biasing of the bias plate in the vicinity of the plasma grid improves the symmetry of the co-extracted electrons and contributes to its stabilzation being thus a promising alternative to potential rods formerly used to achive high performance. With the replacement of the high-voltage power supply at ELISE first 100 s steady state extraction is demonstrated increasing the relevance of the test facility for ITER and DEMO studies. For the latter, the IPP contributions focus on improvement of the RF coupling, the caesium management and conceptual studies of a beam driven plasma neutraliser as alternative to the gas neutraliser system.